Communication Strategy for Learning Process Based on Information Technology at Putra Pertiwi Education Foundation - Ika Yuliasari; Novianty Elizabeth (GoAcademica Research & Publishing, 2023)
Government regulations of the Republic of Indonesia stated that the learning process can be carried out online. On-site communication between educators and students that turns into virtual communication created obstacles and changes in communication interactions. This study is focused on communication strategies in the learning process based on the reality of communication in the field of education which was carried out during the Covid-19 pandemic. The purpose of this study is to examine the communication interaction activities in the learning process and communication strategies that were applied by educators in the learning process during the Covid 19 pandemic at Putra Pertiwi Education Foundation, South Tangerang. We applied a descriptive method with a qualitative approach. Data collection was carried out using survey methods, Forum Group Discussion and interviews. The results showed that, communication interactions in the classroom can take place online, on-site and a blended online and on-site combination. The teachers and students are able to communicate with the help of technology. The communication strategy implemented is related to the teacher's social competence factors, the preparation of innovative messages, the selection of social media platforms, teacher's understanding of student communication behaviour and management of student feedback in interactions.